Predicting seasonal ocean variability around New Zealand using a coupled ocean-atmosphere model. Issue 2 (3rd April 2019) - de Burgh-Day, Catherine O.; Spillman, Claire M.; Stevens, Craig; Alves, Oscar; Rickard, Graham
ABSTRACT: We present a first assessment of the Sea Surface Temperature (SST) and 300m Heat Content (HC) ensemble mean skill of the Australian Community Climate and Earth-System Simulator-Seasonal v1.0 (ACCESS-S1) around New Zealand on seasonal timescales, using a set of retrospective ensemble forecasts for 1990-2012. This was verified against Reynolds AVHRR analysis and Bluelink ReANalysis 3.5 (BRAN3.5). For inshore areas with depth <300m, the model shows skill forecasting for summer at a lead time of 0 months, with 66% and 65% of model grid cells having correlation coefficients exceeding 0.6 for SST and 300m HC respectively. Regions of lower skill seem to be associated with the model representation of the complex and variable frontal systems around New Zealand, and an overly-strong response to the El Niño Southern-Oscillation (ENSO). Nevertheless, the skill of ACCESS-S1 around New Zealand suggests there is potential for the development of useful seasonal forecast products for the region.